Substrate specificity of L-delta-(alpha-aminoadipoyl)-L-cysteinyl-D-valine synthetase from Cephalosporium acremonium: demonstration of the structure of several unnatural tripeptide products. - Baldwin, J; Shiau, C; Byford, M; Schofield, C (1994)
Potential substrates for L-delta-(alpha-aminoadipoyl)-L-(cysteinyl)-D-valine (ACV) synthetase were initially identified using both the amino-acid-dependent ATP<-->pyrophosphate exchange reaction catalysed by the enzyme and the incorporation of 14C-radiolabelled cysteine and valine into potential peptide products. S-Carboxymethylcysteine was an effective substitute for alpha-aminoadipate and both allylglycine and vinylglycine could substitute for cysteine, indicating that the thiol group of cysteine is not essential for peptide formation. L-allo-Isoleucine but not L-isoleucine substituted effectively for valine. The structures of the presumed peptide products derived from these amino acids were confirmed by combined use of electrospray-ionization m.s. (e.s.m.s.) and 1H n.m.r. These results clearly indicate that, in common with other peptide synthetases, but in contrast with ribosomal peptide synthesis, ACV synthetase has a relatively broad substrate specificity.